Synthetic Model Combination: A new machine‐learning method for pharmacometric model ensembling - Alexander Chan; Richard Peck; Megan Gibbs; Mihaela van derSchaar (Wiley, 2023)
Abstract When aiming to make predictions over targets in the pharmacological setting, a data‐focused approach aims to learn models based on a collection of labeled examples. Unfortunately, data sharing is not always possible, and this can result in many different models trained on disparate populations, leading to the natural question of how best to use and combine them when making a new prediction. Previous work has focused on global model selection or ensembling, with the result of a single final model across the feature space. Machine‐learning models perform notoriously poorly on data outside their training domain, however, due to a problem known as covariate shift, and so we argue that when ensembling models the weightings for individual instances must reflect their respective domains-in other words, models that are more likely to have seen information on that instance should have more attention paid to them. We introduce a method for such an instance‐wise ensembling of models called Synthetic Model Combination (SMC), including a novel representation learning step for handling sparse high‐dimensional domains. We demonstrate the use of SMC on an example with dosing predictions for vancomycin, although emphasize the applicability of the method to any scenario involving the use of multiple models.